Peran Stress Kerja Dalam Memediasi Pengaruh Beban Kerja Terhadap Perilaku Cyberloafing Di Pdam Ketapang - Caniago, Albertus Johndeo; Dewi, Yustina Erti Pravitasmara (Universitas Hamzanwadi, 2023)
Cyberloafing is the use of internet access by employees that is not related to work. Work stress can be an aspect that causes cyberloafing behavior with the support of the social environment and stress. This research aims to determine the analysis of work stress as a mediating workload variable and its influence on Cyberloafing behavior. This research approach uses quantitative methods with a questionnaire as a research instrument. The sample studied was 50 online respondents with the sampling technique used, namely random sampling. Validity and reliability tests were carried out to ensure the questionnaire was valid or reliable and technical data analysis used the classic assumption test with the SPSS version 16.0 program. The research results show that there is no positive influence between workload on Cyberloafing. work stress was unable to mediate the influence of workload on PDAM Ketapang Regency Cyberloafing behavior. Efforts to manage work stress, such as providing adequate organizational support, skills training, and recognition for good work, can help reduce work stress and reduce the potential for cyberloafing behavior.